Arábia Saudita e Segurança Regional após as Revoltas no Mundo Árabe - Marco Cepik; Pedro Borba; Pedro Brancher (Meridiano 47, 2017)
This article analyzes the main challenges of Saudi Arabia’s foreign and security policy. Considering the recent unrests in the Arab world, it is clear that, beyond de Iranian projection, the threat of internal riots also becomes a priority item on the Saudi security agenda.